2011
DOI: 10.1002/ibd.21363
|View full text |Cite
|
Sign up to set email alerts
|

Information needs and preferences of recently diagnosed patients with inflammatory bowel disease

Abstract: Given the large number of topics judged by patients to be important and the complexity of the information required, it would be very difficult to communicate this information in oral discussion during typical consultation visits. Supplementing physician-patient consultations with well-designed written information or a Website recommendation may produce more effective communication and education. Patients rated these sources of information as having a high level of acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 31 publications
8
112
0
2
Order By: Relevance
“…According to the analysis performed in this study of patient satisfaction during the first two months following diagnosis, 24% were dissatisfied, 31% moderately satisfied, and 45% very satisfied. 8 Results similar to those of our study were reported by Limdi et al 13 based on a survey of 160 IBD patients in the United Kingdom. Gastroenterologists were the first information source for 83% of patients surveyed, with a degree of satisfaction of 54.1%, followed by general practitioners (54.3%) and the Internet (40%).…”
Section: Rankingsupporting
confidence: 92%
“…According to the analysis performed in this study of patient satisfaction during the first two months following diagnosis, 24% were dissatisfied, 31% moderately satisfied, and 45% very satisfied. 8 Results similar to those of our study were reported by Limdi et al 13 based on a survey of 160 IBD patients in the United Kingdom. Gastroenterologists were the first information source for 83% of patients surveyed, with a degree of satisfaction of 54.1%, followed by general practitioners (54.3%) and the Internet (40%).…”
Section: Rankingsupporting
confidence: 92%
“…Patient videos had the most requests for further information 8 in the comments with 28% of the total comments. PA videos had further information requests in 13.3% of comments and HCP videos had this in 25.9% of the total comments.…”
Section: Resultsmentioning
confidence: 99%
“…Patients may seek health information from the internet at least as frequently as from their gastroenterologist (38% vs 36% respectively) 8 . A key principle in the consent process is to give the patient time to consider their decision by conducting further research -both with extra reading and searching the internet 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with IBD want information about diet and its relationship to their disease but at present we often have little to offer [24] . In considering the emergence of IBD in the developed world decades ago with only relatively recent emergence in the developing world and developed countries in Asia, it is tempting to speculate that differences in diet between these countries has played a role.…”
Section: Dietmentioning
confidence: 99%
“…Patients have concerns about whether stress impacts on their disease and get little information about it [24] . The literature suggests that the perception of stress may impact on disease [38] .…”
Section: Stressmentioning
confidence: 99%